Red-light-emitting polymer composite based on PVDF membranes and Europium phosphor using Buriti Oil as plasticizer - Bispo-Jr, Airton Germano [UNESP]; Oliveira, Nagyla Alves [UNESP]; Cardoso, Celso Xavier [UNESP]; Lima, Sergio Antonio Marques [UNESP]; Job, Aldo Eloizo [UNESP]; Osorio-Román, Igor Orlando [UNESP]; Danna, Caroline Silva [UNESP]; Pires, Ana Maria [UNESP] (Elsevier, 2018)
Rare-earth-doped phosphors immobilized in polymeric matrices find many applications like LEDs. However, little emphasis has been paid to the phosphor and plasticizer effect on the polymer structural, morphological and spectroscopic properties, for the development of functional devices. In this study, we are reporting for the first time the use of Buriti Oil (BO), a natural oil, as plasticizer in Ba2SiO4:Eu3+-doped PVDF composites membranes. Both, Buriti oil and phosphor amount were varied in the membrane synthesis. The drying temperature at 60 °C leads to the formation of the α-PVDF and the increase of the amount of BO up to 400 μL decreases the PVDF crystallinity. Furthermore, the BO and phosphor additions increase the membrane thermal stability. Finally, the composite obtained with 10 wt% of Ba2SiO4:Eu3+ shows relative intense red emission with maximum at 612 nm originating from the Eu3+ radiative transitions in Ba2SiO4 lattice, making this composite material a good candidate for optical devices.
Keywords: Ba2SiO4:Eu3+; Buriti oil; Luminescent membrane; Natural plasticizer; PVDF